PERANCANGAN SISTEM PENDAFTARAN PEMASANGAN KWH BARU DI PLN ULP PAMEKASAN BERBASIS WEB - Ahmadaniyas Solihen; Masdukil Makruf; Busro Akramul Umam (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Electrical energy is an important requirement, used in various devices. The need for electrical energy continues to increase, and the government is responsible for fulfilling it. PT PLN, a state-owned enterprise, is tasked with providing electricity. PLN Pamekasan is a Customer Service Unit in Pamekasan Regency, which aims to provide stable and adequate electricity supply. PLN ULP Pamekasan also provides new KWH installation services. The customer must submit an application and fulfill the required document requirements. The registration process is time consuming and costly. Therefore, to facilitate customer access in carrying out the registration process, the authors plan to design a WEB-based Registration System for New KWH Installation at PLN ULP Pamekasan. This system allows customers to register independently through the website, without having to come to the PLN office. This will save time and transportation costs. Customers can also monitor the installation process in real-time. This system has been tested using black box testing and the PIECES method questionnaire with valid results and an average satisfaction value of 4.560 using the Kaplan and Norton models. It is hoped that this system will improve PLN's service to customers and advance the electricity sector in Indonesia.